Labor-Friendly Corporate Practices: Is What is Good for Employees Good for Shareholders? - Faleye, Olubunmi; Trahan, Emery A. (2011)
As corporate managers interact with non-shareholder stakeholders, potential tradeoffs emerge and questions arise as to how these interactions impact shareholder value. We argue that this shareholder–stakeholder debate is an important issue within the overall corporate governance and corporate policy domain and examine one such stakeholder group – employees – by studying labor-friendly corporate practices. We find that announcements of labor-friendly policies are associated with positive abnormal stock returns. Labor-friendly firms also outperform otherwise similar firms, both in terms of long-run stock market returns and operating results. In addition, we find that the probability and benefits of labor-friendliness increase with the demand for highly skilled labor. Our analysis of excess executive compensation suggests that top management derives no pecuniary benefits from labor-friendly practices. We interpret our results as consistent with a genuine concern for employees translating into higher productivity and profitability, which in turn facilitate value creation. It appears that the benefits of labor-friendly practices significantly outweigh the costs and that what is good for employees is good for shareholders.
Keywords: Agency Theory; Stakeholder Theory; employee stakeholders; Corporate Social Responsibility